The impacts of the university policies during covid-19 pandemic towards academic operation, financial, facilities and staff operation in universiti malaysia pahang: A dematel based model - Azrizulazmi, Bustan (2022)
The spread of the COVID-19 virus, which is said to have started in Wuhan, China and spread around the world, has paralysed the economy in some countries. Business activities could not be carried out; workers were only allowed to work from home as a result of movement control orders; death rates were rising due to the COVID-19 virus; and poverty and unemployment rates were rising worldwide. In Malaysia, the spread of the COVID-19 virus has also spread throughout the country since early March 2020 and has disrupted the country's growth and economy. As a result of the spread of the COVID-19 virus and the Movement Control Order (PKP) implemented by the Malaysian government to curb the infection of COVID-19 among Malaysians, it has impacted and changed the landscape of the country's higher education system. This case study aims to look at the implications for policy at the university during the COVID-19 period on the academic, financial, facility, and staff operations at Universiti Malaysia Pahang (UMP). This study will refer to some of the policies that have been developed by the UMP during the COVID-19 pandemic to address the problems and issues related to the operation of the UMP. This case study involved a total of 15 respondents, consisting of University Top Management, Dean and Deputy Dean (Academic) in the Faculty, Directors in the Strategic Center and Academic Services, Finance Manager, and Manager in the Human Resources Division. The process of recording and sampling data is done using qualitative methods through the process of interviews and closed guide questionnaires involving sections related to demographics, the effectiveness of the implementation of a policy developed by the university, and the impact of the policy on university operations. After that, the data was analysed using the Relative Importance Index (RII), and the results from RII will determine which policy has the best implementation effectiveness rate in UMP. Questionnaires conducted for data collection were also conducted to identify the relationship between each policy. The survey questions used were based on DEMATEL. DEMATEL was used to analyse the second data collection from the respondents. Using the DEMATEL method, the relationship between each policy can be identified and a framework based on the relationship can be devised. The policies that impact the operation of the university have been demonstrated within the framework. The policies that impact and influence the operation of the university are online teaching and learning. Meanwhile, the policies that have less impact on the operation of the university are the policy of reducing the accommodation fee rate for students who are on campus.